Musical performance within the music therapy process with people having autism - Gattino, Gustavo (Tidsskriftet Dansk Musikterapi, 2018)
At the request of the Danish Journal of Music Therapy, I will present some considerations on music therapy for people with autism spectrum disorder (ASD) in Brazil. My main focus is to present and discuss the role of musicals performed by clients with ASD as a part of the music therapy process, as this new trend in Brazil could inspire Danish clinicians.